Hermeneutika dalam Ilmu-Ilmu Humaniora dan Agama: Model, Pengembangan dan Metode Penelitian - Ali Anhar Syi'bul Huda; Abid Nurhuda; Nur Aini Setyaningtyas; Muhammad Imam Syafi'i; Farhan Akmala Putra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This study aims to describe the description of hermeneutics as a model of scientific research, the development of humanities sciences and as a research method in religious sciences The method used is a literature study with a qualitative approach. Then analyzed descriptively. The results showed that hermeneutics emerged a long time ago during the ancient Greek civilization and was more dominant in activities in understanding the scriptures but in its development it could reach the humanities and religious sciences. In addition, it also acts as a bridge to bring together hermeneutical theory with qualitative empirical research and symbols that are difficult for humans to understand in the symptoms of the universe. Therefore, hermeneutics is able to interpret and reveal the meaning of the text by considering the social, cultural, and historical context. And of course this is very useful in revealing divine messages through scriptural texts that still need explanation so that they do not make mistakes in practicing God's teachings.